2021
DOI: 10.2196/19958
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Apps for Dental Caries Prevention: Systematic Search and Quality Evaluation

Abstract: Background Dental caries is the most common multifactorial oral disease; it affects 60% to 90% of the global population. Dental caries is highly preventable through prevention behaviors aimed at improving oral hygiene, adequate fluoride usage, and dietary intake. Mobile apps have the potential to support patients with dental caries; however, little is known about the availability, target audience, quality, and features of these apps. Objective This review aims to system… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 51 publications
0
37
1
Order By: Relevance
“…Sharif et al (2019) [ 43 ] and Parker et al (2019) [ 44 ] included 20 patient-focused oral hygiene apps available on the United Kingdom Apple App Store and Google Play store. Chen et al (2021) screened apps focusing on dental caries self-management behaviors, including oral hygiene, dietary intake, and fluoride usage [ 45 ]. They performed their research in the Australian iTunes and Google Play App stores and included 18 apps in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Sharif et al (2019) [ 43 ] and Parker et al (2019) [ 44 ] included 20 patient-focused oral hygiene apps available on the United Kingdom Apple App Store and Google Play store. Chen et al (2021) screened apps focusing on dental caries self-management behaviors, including oral hygiene, dietary intake, and fluoride usage [ 45 ]. They performed their research in the Australian iTunes and Google Play App stores and included 18 apps in their study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mobile application was directedly focused on pre-schoolers and featured gamification, and the usability testing was conducted with satisfaction interview and observation suitable to their target group. In fact, the most recent systematic search and quality appraisal study concluded that there was no high-quality mobile applications aimed at parents to highlight the particular dental caries preventive activities for children aged 6 years and below [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Descriptive statistical analysis of the uMARS rating was used to gain insights into the usability experience of the participants with ASD. Many studies have used the uMARS questionnaire to evaluate the usability of developed apps [ 35 - 37 ].…”
Section: Methodsmentioning
confidence: 99%